The ALMA survey to Resolve exoKuiper belt Substructures (ARKS) IV. CO gas imaging and overview - Perez-Marquez, S (EDP Sciences, 2026)
Context. CO gas is detected in a significant number (~20) of debris discs (exoKuiper belts), but understanding its origin and evolution remains elusive. Crucial pieces of evidence are its mass and spectro-spatial distribution, which are coupled through optical depth and have only been analysed at low to moderate resolution so far. The ALMA survey to Resolve exoKuiper belt Substructures (ARKS) is the first ALMA large program to target debris discs at high spectro-spatial resolution. Aims. We used 12CO and 13CO J=3-2 line data of 18 debris belts observed by ARKS, 5 of which were already known to be gas-bearing, in order to analyse the spectro-spatial distribution of CO and constrain the gas mass in discs that were known to host gas previously, and to search for gas in the remaining 13 discs without previous CO detections. Methods. We developed a line-imaging pipeline for ARKS CO data with a high spectro-spatial resolution. Using this tool, we produced line cubes for each of the ARKS targets, with a spatial resolution down to about 70 mas and a spectral resolution of 26 m s−1. We used spectro-spatial shifting and stacking techniques to produce a gallery of maps with the highest possible signal-to-noise ratio (S/N) and with radial and spectral profiles that reveal the distribution and kinematics of gas in five gas-bearing discs at unprecedented detail. Results. For each of the five gas-bearing discs (HD 9672/49 Ceti, HD 32297, HD 121617, HD 131488, and HD 131835), we constrained the inner radius of the 12CO (r min ~ 3-68 au), and we found that the radial brightness profile of CO peaked interior to the dust ring, but that CO was also more radially extended than the dust. In a second-generation scenario, this would require significant shielding of CO that would allow it to viscously spread to the observed widths. We present the first radially resolved 12CO/13CO isotopologue flux ratios in five gas-bearing debris discs and found them to be constant with radius for the majority (four out of five) of systems. This indicates that 12CO and 13CO are both optically thick or optically thin throughout the discs. We report CO line fluxes or upper limits for all systems and optical depth dependant masses for the five systems with detected CO. Finally, we analysed the 12CO J=3-2 line luminosities for a range of ARKS debris discs and for debris discs from the literature. We confirm that gas is mostly detected in young systems. However, the high scatter seen in young/high fractional luminosity systems indicates no trend within the systems with detected gas. This could be caused by different system properties and/or evolution pathways. © The Authors 2026.